Bangladesh - Prices of Essential Commodities : Recent Trends, Underlying Factors and Policy Options - World Bank (Washington, DC, 2012)
There is a concern in Bangladesh that prices of essential commodities, mainly food items including rice, wheat, pulses, sugar, edible oils, ginger, garlic, onion and potato, have shown an upward trend in the past several months. Media reports in recent weeks are full of government actions including pictures of personnel of Bangladesh rifles manning fair price shops and selling essential food items to the lower and lower-middle income classes. The government's concern of the impact of rising food prices on the welfare of the poor is quite understandable. According to the 2005 household and income expenditure data, these food items account for more than one-third of the annual household expenditure of the bottom 20 percent of the population. What is the true picture of rising food prices in Bangladesh? How much of the rise is due to changes in demand and supply in the international commodity markets? What domestic factors, particularly in the very short-run, i.e., a week to ten days, account for the price rise? What measures has the Government of Bangladesh taken to check the price rise and what other options exist to deal with the prevailing situation? This note addresses these questions.